2003
DOI: 10.1128/aac.47.6.1958-1962.2003
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antimicrobial Resistance in Rapidly Growing Mycobacteria in Taiwan

Abstract: An increasing number of clinical isolations of rapidly growing mycobacteria (RGM) at the National Taiwan University Hospital were noted from 1992 to 2001. Broth microdilution MICs of 15 antimicrobial agents were determined for 200 clinical isolates of RGM, including the Mycobacterium fortuitum group (69 isolates), M. chelonae (39 isolates), and M. abscessus (92 isolates). Our results showed that the resistance rates of these isolates to the currently available agents were remarkably high. Amikacin was active a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 30 publications
5
62
4
Order By: Relevance
“…Another study found that MFLX was active against M. abscessus and that a combination of CAM and MFLX was effective against M. abscessus strains in in vitro models (10). Moreover, some M. abscessus isolates are susceptible to the oral drug linezolid (35,38). However, linezolid was rarely used in our survey to treat M. abscessus species lung disease because of the high cost and moderate to severe side effects in Japan.…”
Section: Discussionmentioning
confidence: 80%
“…Another study found that MFLX was active against M. abscessus and that a combination of CAM and MFLX was effective against M. abscessus strains in in vitro models (10). Moreover, some M. abscessus isolates are susceptible to the oral drug linezolid (35,38). However, linezolid was rarely used in our survey to treat M. abscessus species lung disease because of the high cost and moderate to severe side effects in Japan.…”
Section: Discussionmentioning
confidence: 80%
“…M. abscessus is also recovered from respiratory specimens of patients with cystic fibrosis (1,4). The differences in antimicrobial susceptibilities between M. abscessus and M. chelonae demand an easy differentiation of these two closely related species (14). Restriction analysis of an hsp65 gene fragment has been used to this end for over 10 years (7,12,13).…”
mentioning
confidence: 99%
“…This limitation has no clinical relevance currently for the diagnosis of infection by M. abscessus except for the possibility of epidemiological analysis in clinical infection. The most important benefit of the ITS PCR assay is the ability to differentiate between M. chelonae and M. abscessus, since infections with these organisms require different treatment regimens (16,17).…”
mentioning
confidence: 99%